Water Vapor Diffusion and Adsorption of Sandstones: Influence of Rock Texture and Composition. (4th July 2016) - Keppert, Martin; Žumár, Jaromír; Čáchová, Monika; Koňáková, Dana; Svora, Petr; Pavlík, Zbyšek; Vejmelková, Eva; Černý, Robert
Abstract : The term sandstone is used for wide range of rocks containing quartz clasts which can be cemented by secondary precipitated quartz or calcite; moreover the space between clasts can be filled by matrix. These facts result in existence of numerous rocks having highly various properties. Sandstones have been used as construction materials due to their good accessibility and workability. Since most of sandstones are porous, water vapor can penetrate through sandstone constructions. The rate of water vapor diffusion, as well as the vapor sorption isotherm, was determined for range of sandstone types. The diffusion resistance factor was found to be dependent on the total porosity of sandstone but the sorption behavior was strongly influenced by nature of the particular sandstone; the specific surface area of stone and presence of clay matrix are determining its sorption isotherm. The published data enable estimating (i) diffusion resistance factor of a sandstone via knowledge of its total porosity and (ii) the sorption isotherm via knowledge of the stone's nature and specific surface area. This approach can significantly reduce the time necessary to acquire vapor-related properties of a sandstone.